Increased non-protein bound iron in Down syndrome: contribution to lipid peroxidation and cognitive decline - Manna, Caterina; Officioso, Arbace; Trojsi, Francesca; Tedeschi, Gioacchino; Leoncini, Silvia; Signorini, Cinzia; Ciccoli, Lucia; De Felice, Claudio (Free radical research, 2016)
Down syndrome (DS, trisomy 21) is the leading cause of chromosomal-related intellectual disability. At an early age, adults with DS develop with the neuropathological hallmarks of Alzheimer's disease, associated with a chronic oxidative stress. To investigate if non-protein bound iron (NPBI) can contribute to building up a pro-oxidative microenvironment, we evaluated NPBI in both plasma and erythrocytes from DS and age-matched controls, together with in vivo markers of lipid peroxidation (F 2 -isoprostanes, F 2 -dihomo-isoprostanes, F 4 -neuroprostanes) and in vitro reactive oxygen species (ROS) formation in erythrocytes. The serum iron panel and uric acid were also measured. Second, we explored possible correlation between NPBI, lipid peroxidation and cognitive performance. Here, we report NPBI increase in DS, which correlates with increased serum ferritin and uric acid. High levels of lipid peroxidation markers and intraerythrocyte ROS formations were also reported. Furthermore, the scores of Raven's Colored Progressive Matrices (RCPM) test, performed as a measure of current cognitive function, are inversely related to NPBI, serum uric acid, and ferritin. Likewise, ROS production, F 2 -isoprostanes, and F 4 -neuroprostanes were also inversely related to cognitive performance, whereas serum transferrin positively correlated to RCPM scores. Our data reveal that increased availability of free redox-active iron, associated with enhanced lipid peroxidation, may be involved in neurodegeneration and cognitive decline in DS. In this respect, we propose chelation therapy as a potential preventive/therapeutic tool in DS.